A Half Century of Student Data Reveals the Professional Impacts of a Biology Field Course. (30th November 2022) - Arcila Hernández, Lina M; Mittan-Moreau, Cinnamon S; Lamb, Todd; Holmes, Katherine D; McDonald, Coby A; Zamudio, Kelly R; Ballen, Cissy J
Abstract: Field courses provide learning experiences that diversify curricula and inspire students. Despite these benefits, we still have much to learn about field course impacts on student outcomes and career trajectories. We used a 50-year longitudinal data set to compare career outcomes for graduate students who participated in a biology field course with those of students who did not. More broadly, we surveyed students to identify graduate experiences most useful to advancing their careers. We found that field course attendees coauthored more scientific publications than did nonattendees. Although the students in both groups graduated and continued on to scientific careers at similar rates, the students attending the field course became faculty at a higher rate. Survey data showed that field courses provide valuable opportunities to graduate students, including student-led environments and mentor feedback. Our findings underscore the importance of field courses as effective tools to train the next generation of scientists.